2019
DOI: 10.1038/s41598-019-51319-1
|View full text |Cite
|
Sign up to set email alerts
|

Sperm function in vitro and fertility after antibiotic-free, hypothermic storage of liquid preserved boar semen

Abstract: The role of antibiotics (AB) in semen extenders as a potential contribution to the global antimicrobial resistance threat is emerging. Here, we establish an AB-free hypothermic preservation strategy for boar semen and investigate its impact on sperm function, microbial load and fertility after artificial insemination (AI). Spermatozoa (12 boars) preserved in AB-free AndroStar Premium extender at 5 °C maintained high motility, membrane integrity, and a low DNA-fragmentation index throughout 72 h storage and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 48 publications
7
83
0
1
Order By: Relevance
“…In this context, it is evident that the temperature is an important factor that can interfere on bacterial dissemination during semen storage, particularly for stallion and boar cooled-semen technology, in which protocols highlight use of a relatively high temperature (15 to 17 °C) in a nutrient-rich extender that can favor bacterial growth. However, it was demonstrated that even for stallions (Price et al, 2008) and boars (Waberski et al, 2019), the hypothermic storage (5 °C) may reduce the use of antimicrobial drugs (Table 1).…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…In this context, it is evident that the temperature is an important factor that can interfere on bacterial dissemination during semen storage, particularly for stallion and boar cooled-semen technology, in which protocols highlight use of a relatively high temperature (15 to 17 °C) in a nutrient-rich extender that can favor bacterial growth. However, it was demonstrated that even for stallions (Price et al, 2008) and boars (Waberski et al, 2019), the hypothermic storage (5 °C) may reduce the use of antimicrobial drugs (Table 1).…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…It is important to consider that the satisfactory in vivo results previously obtained 5 were from sows inseminated with heterospermic doses from pools of a total of 23 boars. Thus, the boar effect was masked to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…For analyses performed during storage, a different semen dose tube was used at each time of evaluation (24, 72, and 120 hours of storage) to avoid the influence of manipulation. Total and progressive motility were assed using a CASA system (AndroVison ® version 1.1.4; Minitüb GmbH) under phase contrast microscopy (200× magnification, Axio Scope.A1, Zeiss ® ) 4,5 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations